Correlación entre el límite líquido y el coeficiente de compresibilidad para arcillas de llanura costera (2016)
The objective of this article is to present an analysis of the statistical correlation existing between the coefficient of compressibility Cc obtained through multiple one dimensional trials and the liquid limit found in soils that are normally consolidated to quickly over consolidated. In addition, the relationship between drainage resistance and preconsolidation strength with a plasticity index within a controlled environment was analyzed. In order to further develop this topic, the geological characteristics of the environment whose subsoil was tested are presented. Next, the exploration methods used to obtain undisturbed samples are presents. Emphasis is made on the results obtained from the laboratory tests done on to physically characterize the clays attained from the study site in the north coast of Colombia in the city of Cartagena. Finally, a comparison and discussion are included on the statistical correlation obtained with respect to different correlations presented by several authors.In function of the analysis done, the use of the existing correlations on clay soils with similar geological origin will be determined.